2019
DOI: 10.1002/phar.2231
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Renal Clearance

Abstract: Augmented renal clearance (ARC) is a phenomenon in critically ill patients characterized by increased creatinine clearance and elimination of renally eliminated medications. Patients with severe neurologic injury, sepsis, trauma, and burns have been consistently identified as at risk of ARC, with mean creatinine clearances ranging from 170 ml/minute to more than 300 ml/minute. Several potential mechanisms may contribute to the occurrence of ARC including endogenous responses to increased metabolism and solute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
131
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(135 citation statements)
references
References 73 publications
2
131
1
1
Order By: Relevance
“…The current simulation suggested that daily doses of 350 0-450 0 mg should be considered for such patients, which is in line with a nomogram previously proposed for critically-ill patients [30] . This may require early identification and separation of ARC patients from the general population, but is feasible as these patients are typically young and with trauma, burn injuries, or acute leukaemia [31,32] . A serum creatinine < 0.4 mg/dL could also serve as a surrogate marker for ARC during the treatment [17] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current simulation suggested that daily doses of 350 0-450 0 mg should be considered for such patients, which is in line with a nomogram previously proposed for critically-ill patients [30] . This may require early identification and separation of ARC patients from the general population, but is feasible as these patients are typically young and with trauma, burn injuries, or acute leukaemia [31,32] . A serum creatinine < 0.4 mg/dL could also serve as a surrogate marker for ARC during the treatment [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Vancomycin is not significantly metabolised in humans. Its elimination primarily depends on renal function [29,32] (with non-renal clearance being probably < 5% of the total drug clearance), which the current model and proposed dosing strategies fully consider, and its plasma levels are not influenced by the activity of renal transport systems [33] . Moreover, all current data were adjusted to a standard creatinine clearance of 100 mL/min for a nominal 70-kg subject, allowing easy comparison and translation to patients with different renal function and weight.…”
Section: Discussionmentioning
confidence: 99%
“…Augmented renal clearance (ARC), referring to enhanced renal elimination, has been identified during the last decade to be of significant clinical importance in patients admitted at the intensive care unit (ICU). Reported incidences for ARC in the ICU vary between 16-100% depending on the subset of patients and the definition employed for ARC [1][2][3][4]. ARC has the potential to result in subtherapeutic plasma levels and consequent therapeutic failure as the kidney is the primary excretory pathway for many (hydrophilic) drugs [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Dosing of medications in CKD patients is further complicated by the very nature of the dose-response interaction for the various medications. Some medications need high peak levels, whereas others require less fluctuation of the levels over the dosing intervals [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. For example, aminoglycoside antibiotics are an example of the former, whereas β-lactams are a representative of the latter [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%